Recovery strategies to optimise adaptations to concurrent aerobic and strength training - Allen, N. G.; Higham, S. M.; Duffield, R. (Concurrent aerobic and strength training. Scientific basics and practical applications, 2019)
Concurrent training involves the combined use of divergent exercise stimuli within either a specific training day or continuing programme. Considerations around acute and cumulative fatigue, antagonistic molecular signalling, and nutrient timing may influence recovery and subsequent adaptation to this mode of training. Thus, attention should be paid to optimal recovery methods to improve training tolerance, maximise adaptations, and limit negative outcomes. This chapter will explore these issues and discuss the efficacy of potential recovery strategies for concurrent training. Specifically, practical strategies relating to fatigue management, nutrition, supplements, sleep, and targeted musculoskeletal recovery interventions will be examined. Finally, evidence-based recommendations are made for recovery in professional and recreational athletes undertaking concurrent training.